The Tuvan population of Usinsk boundary district of the Yenisei province. From the history of relations between Russia and Tuva - Dazishen, Vladimir G. (The New Research of Tuva, 2009)
Basing on archival documents the author unveils insufficiently known question in the history of mutual relations between Tuva and Russia. The territory of Usinsk valley became «the first line» in interaction and cooperation between Russians and Tuvans. In the 19th and the beginning 20th centuries a considerable number of Tuvans lived in a southern parts of the Yenisei province of Russian Empire. They were not considered by Russian authorities, it did not cause serious problems and contradictions at the international level between Russia and China.
Keywords: Russia; China; Tuva; Usinskaya valley; coexistence; culture; Russian